Career analysis of youth talent Brazilian soccer players - Drezner, R.; Aguilar Cortez, J. A.; Simoes, A. C.; Dantas, L. (World Congress of Performance Analysis of Sport IX, 2012)
The aim of this study was to analyze the future career of young talents in Brazilian soccer to assess the variation in performance between the transitions from youth to adult teams. The sample consisted of 154 players who competed in the under 17 FIFA World Cup for Brazil between 1995 and 2009. We used six rating categories for assessing payers career success : 1 - Participation in the World Cup, 2 - Play in Brazilian National Team, 3 - Long career in the big leagues, 4 - Short career in the big leagues, 5 - Only play in the minor leagues, 6 - Did not play professional soccer. It was determined a minimum of 150 games to rank this success as long as 30 short. For younger players the number of matches was reduced in 2005 (75, 30), 2007 (50, 20) and 2009 (30, 10). The results showed that most of the players could not play major leagues (71, 46.1%) or had short career (40, 25.97%). Only four players (2.6%) played the World Cup, 16 (10.39%) played for the Brazilian team and 23 (14.94%) had long-standing success. All players have turned professional. With these results we conclude that the most talented players failed to maintain the success achieved in football adult.